Sinergi antara komunikasi dan kepemimpinan dalam membangun tim yang sehat pada proyek sistem informasi - Naila Yustiara; Raines Respati, Azka Acuzio; Nurmiati, Evy (IT Explore: Jurnal Penerapan Teknologi Informasi dan Komunikasi, 2026)
The success of information systems projects in the digital transformation era is often hindered by unhealthy team dynamics, even when technical aspects have been optimally met. This study aims to analyze the synergy between inclusive communication strategies and digital leadership styles in building team health and sustainable performance. The research method employed is a qualitative literature study, integrating variables such as digital leadership, psychological safety, and knowledge management. The results indicate that digital leadership serves as a primary catalyst in creating a psychologically safe work environment, which in turn enhances the creative self-efficacy of team members. Synergy is effectively established when leaders adopt transparent communication channels through digital collaboration tools to mitigate role conflict and technostress within hybrid work environments. Furthermore, knowledge coordination is proven to strengthen team cohesiveness through the conversion of personal knowledge into strategic organizational assets. The study concludes that the integration of empathic communication and adaptive leadership is the fundamental basis for the cognitive, psychological, and operational health of the team. This research produces a managerial synergy framework to mitigate the risk of project failure caused by human factors in the digital era.